2021
DOI: 10.1021/acs.cgd.1c00991
|View full text |Cite
|
Sign up to set email alerts
|

GABA-Controlled Synthesis of the Metastable Polymorphic Form and Crystallization Behavior with a Chiral Malic Acid

Abstract: The controlled pH-based crystallization approach with acetic acid to the pharmaceutical interesting metastable polymorph II of the API γ-aminobutyric acid (GABA), which is hitherto accessible by sublimation under reduced pressure and high temperature, is described. Furthermore, the synthesis and single crystal characterization of a nonhydrated chiral [GABA-H][malate] compound is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Now, if lattice energies were the only indicator of phase stability, II - 1 and IV - 2 should easily undergo phase transitions to I - 1 and II - 2 , respectively. Indeed, a monotropic phase transition partially occurs by sublimation of I -GABA [ 43 ], but crystallization of this form from an aqueous solution with acetic acid or by liquid-assisted grinding with acetic acid leads to a stable II - 1 product [ 42 , 45 ]. The 2 polymorphs can be obtained from different solvents, but influences such as temperature treatment or mechanical stress can also induce an enantiotropic solid–solid phase transition [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Now, if lattice energies were the only indicator of phase stability, II - 1 and IV - 2 should easily undergo phase transitions to I - 1 and II - 2 , respectively. Indeed, a monotropic phase transition partially occurs by sublimation of I -GABA [ 43 ], but crystallization of this form from an aqueous solution with acetic acid or by liquid-assisted grinding with acetic acid leads to a stable II - 1 product [ 42 , 45 ]. The 2 polymorphs can be obtained from different solvents, but influences such as temperature treatment or mechanical stress can also induce an enantiotropic solid–solid phase transition [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Vasceq et al showed polymorphs of GABA to perform different permeabilities in crossing the blood−brain barrier, where the metastable II -GABA modification exhibits higher bioactivity [ 43 ]. Wang et al reported strategies of additive-induced and liquid-assisted mechanochemical GABA polymorph control [ 42 , 44 ], followed by Lamkowski et al, who discussed the pH influences on the stabilization of II -GABA in 2022 [ 45 ]. A plethora of pharmaceutically active ingredients (APIs) are derived from GABA, such as pregabalin, phenibut, baclofen, and gabapentin, which have all been discussed regarding their crystal structure over time [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations